2021
DOI: 10.9734/jpri/2021/v33i1831311
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antifungal Activity of Ficus carica Plant Extract

Abstract: The development of antibiotic resistant bacteria causes many harmful effects on human and animal lives. In developing countries many expensive synthetic drugs are being used to cure diseases but they have many side effects. Therefore, there is need to develop new strategies to control microbial infections. Therefore, we decided to work on extracts of different parts of Ficus carica which have good activity against gram positive bacteria, gram negative bacteria and fungal species. Methanol and chloroform extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…Based on the appearance of colonies, Gram staining and some biochemical tests ,bacterial colonies were identified (5) To isolate Salmonella bacteria, it was inoculated in tetrathionate or selenite broths media for 24 hours at 37°C. (0.1 ml) of this microbial culture were placed in Dextrose Lysine for 24 hours at 37°C.…”
Section: Microbial Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the appearance of colonies, Gram staining and some biochemical tests ,bacterial colonies were identified (5) To isolate Salmonella bacteria, it was inoculated in tetrathionate or selenite broths media for 24 hours at 37°C. (0.1 ml) of this microbial culture were placed in Dextrose Lysine for 24 hours at 37°C.…”
Section: Microbial Analysismentioning
confidence: 99%
“…Many studies evaluated the antibacterial effects of different parts of F. carica when used to inhibit activity against two gram-positive bacteria and two gram-negative bacteria, for instance ethanolic extract from leaves of F. carica latex had a strong antibacterial effects at different concentrations against Enterococcus faecalis in the infected dentinal tubules when used as intracanal medicaments. Whilst another study indicated the inhibiting effectiveness against Aspergillus oryzae [5]. Other studies showed that a minimum inhibitory concentration of ethanolic extract of the leaves of F. carica against Streptococcus pyogens, Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, and Klebsiella pneumoniaewere noticed at 5% concentration [6,4].…”
Section: Introductionmentioning
confidence: 97%
“…Flavonol, flavon, dan antosianin diketahui memiliki aktivitas yang sinergis terhadap antijamur (11). Sebuah penelitian yang dilakukan di pakistan (12) menunjukan buah tin (Ficus carica L.) memiliki aktivitas sebagai antijamur. Berdasarkan latar belakang tersebut maka akan dilakukan penelitian terhadap buah tin (Ficus carica L.) yang diperoleh dari Indonesia terhadap jamur Aspergillus niger.…”
Section: Aunclassified
“…6 Several studies have been conducted to examine the biological activities of fig leaves, such as antioxidant, antimicrobial, anticancer, hepatoprotective, antipyretic, hypoglycemic, anti-hyperlipidemic, and antimutagenic. [7][8][9][10][11][12][13] Some reports also showed that the antioxidant activity of this plant dissimilar with different solvent extraction. 14,15,16 This study was developed to compare the phytochemical compounds of F. carica Linn leaves that was originated from Binjai city, Indonesia with two different extraction solvents which have almost similar polarity.…”
Section: Introductionmentioning
confidence: 99%